Directional accuracy for inflation and unemployment rate predictions in Romania - Mihaela Simionescu (International Journal of Economic Sciences and Applied Research, 2014)
The main objective of this study is to assess the usefulness and rationality of the inflation and unemployment rate forecasts made for Romanian by three experts in forecasting: F1, F2 and F3. All the unemployment rate forecasts over the horizon 2001-2013 provided by all experts do not provide valuable information for future decisional process. According to Pesaran-Timmermann test, the directional forecasts of F3 and the autumn expectations of F2 are useful and rational.
Keywords: C52; C53; E27; E37; 330; forecasts; directional accuracy; inflation rate; unemployment rate